How Far is Consumer Protection in the Health Care Sector? - Cut Mayang Widya Nuryaasiinta (Unnes Law Journal, 2020)
In health services, it is not uncommon to cause malpractice due to negligence committed by health workers who are not in accordance with professional standards. This paper is intended to analyse concerning to how to protect consumers, the form of legal protection for patients as consumers of medical services and the forms of responsibility of hospitals and doctors as parties to medical services according to Law No. 8 of 1999 concerning Consumer Protection and Law No. 36 of 2009 concerning Health. To answer the question used the normative legal research method, the approach used in legal research is the statute approachÂÂ), and case approach. In the Decision of Central Jakarta District Court No. 287/PDT.G/BTH/2011/PN.JKT.PST) there are 5 (five) rights of consumers who have been neglected by business actors according to Law Number 8 of 1999 concerning Consumer Protection, namely Article 4 points (a), (c), (d), (e), (g), and (h), and according to the Law Number 36 of 2009 concerning Health of consumer rights that are violated is in Articles 5-8, Articles 56-58. Regarding the responsibility given by business actors (RSCM) to consumers (Nina Dwijayanti) in the form of money amounting to Rp 1,776,010,000.00 (one billion seven hundred seventy-six million ten thousand rupiah), in Article 19 paragraph (2) the Consumer Law only recognizes just material compensation but according to Article 46 of Law No.44 of 2009 concerning this compensation house is appropriate.